General Socio-Economic Features of the Regions and Regional Policy in Bulgaria - Todorov, Vyacheslav (Journal of Danubian Studies and Research, 2025)
Abstract: The policy of the Republic of Bulgaria is aimed at preserving territorial integrity based on national interests, national culture, the protection of constitutional rights and freedoms of citizens, and equal rights and opportunities for personal development regardless of ethnic or religious affiliation. The local self-government system in Bulgaria does not fully comply with all the parameters of the European Charter of Local Self-Government. The need for further development at the regional level is primarily due to the fact that the consolidated budget limits the rights of municipalities, and the level of financial self-sufficiency of communities is low by EU standards (in most communities, more than half of the budget consists of subsidies), along with an insufficiently clear distinction between delegated and own competences of local authorities. Several key issues are linked to decentralization and the development of Bulgarian communities. A sharp decline in population in peripheral areas of basic administrative-territorial units of local self-government, high levels of unemployment, low educational attainment, closure of old industries, and the predominance of extractive industries, metallurgy, and the chemical industry are causing drastic negative trends in people’s living conditions. Overall, the problems of local self-government development in Bulgaria – especially at the community level – are largely similar to those faced by Ukraine. However, our country not only fails to consider Bulgaria’s experience, but continues to make new and recurring mistakes.